2000
DOI: 10.1128/jcm.38.2.789-794.2000
|View full text |Cite
|
Sign up to set email alerts
|

Application of 16S rRNA Gene Sequencing To Identify Bordetella hinzii as the Causative Agent of Fatal Septicemia

Abstract: We report on the first case of fatal septicemia caused byBordetella hinzii. The causative organism exhibited a biochemical profile identical to that of Bordetella aviumwith three commercial identification systems (API 20E, API 20 NE, and Vitek GNI+ card). However, its cellular fatty acid profile was not typical for either B. avium or previously reported strains of B. hinzii. Presumptive identification of the patient's isolate was accomplished by traditional biochemical testing, and definitive identification wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…In cases where the genus and species could not be correctly identified with these methods, or when the results obtained by the MALDI-TOF MS and conventional methods were discordant, PCR and sequencing of the 16S rRNA gene were performed for definite identification, as described previously. 8 In addition, MALDI-TOF MS analyses were also performed on subcultured colonies derived from the positive blood culture bottles ('indirect' method) for comparison with the direct identification method.…”
Section: Reference Methods For Bacterial Identificationmentioning
confidence: 99%
“…In cases where the genus and species could not be correctly identified with these methods, or when the results obtained by the MALDI-TOF MS and conventional methods were discordant, PCR and sequencing of the 16S rRNA gene were performed for definite identification, as described previously. 8 In addition, MALDI-TOF MS analyses were also performed on subcultured colonies derived from the positive blood culture bottles ('indirect' method) for comparison with the direct identification method.…”
Section: Reference Methods For Bacterial Identificationmentioning
confidence: 99%
“…The nucleotide sequence (1457 bp) of the 16S rRNA gene of strain 10d was 96.7% identical with that of Bordetella avium DSM 11334 T (accession no. AF177666), 96.7% identical with that of Bordetella hinzii DSM 4922 T (AF177667), and 96.0% identical with that of Bordetella bronchiseptica (AJ278452) [26,27]. This close phylogenic relatedness with other members of the genus Bordetella [27,28] was also reflected in the following characteristics of strain 10d: the DNA GC content was 67.0 mol%, the isoprenoid quinone Q-8 was detected, tetrazolium was reduced, nicotinamide was required for growth and potassium tellurite inhibited growth.…”
Section: Identification Of a 4-amino-3-hydroxybenzoate-assimilating Omentioning
confidence: 99%
“…However, for most clinical bacterialisolates the initial 500-bp sequence provides adequate differentiation for identification and in fact can provide a bigger percent difference between strains because the region shows slightly more diversity per kilobase sequenced. Kattar et al (2001) found that 66% of the variability in the 16 S rRNA gene sequence among Bordetella species was in the first 500 bp. Evaluations published in the literature, made using the microseq database (AppliedBiosystems Inc. [ABI], Foster City, Calif.), are usually based on the 500-bp sequence (Tang et al, 1998;Patel et al, 2000;TangHall et al, 2000;Hall, et al, 2003).…”
Section: Discussionmentioning
confidence: 99%